Wisata Kelautan Berkelanjutan di Labuanbajo, Nusa Tenggara Timur: Sebuah Study Tentang Persepsi Masyarakat Kawasan Pesisir - Alexander M. A. Khan; Imam Musthofa; Indarwati Aminuddin; Fitri Handayani; Ratna N. Kuswara; Ajeng Wulandari (JURNAL MASTER PARIWISATA, 2020)
Community-based tourism is one type of tourism that involves community participation to achieve the goal of sustainable tourism development. The purpose of this study is to determine the tourism potential to be managed by the community based on people's perceptions of the existing tourism potential, as well as identifying people's perceptions of national, regional, and also traditional policies in tourism. This research was divided into several data collection, internal-external factor analysis, data analysis and development strategy analysis using the SWOT matrix. The conclusions of this study are (1) Natural resources in Labuan Bajo which can be used as tourist attractions that have not been managed and developed properly. Those are Ara Mountain, Ina Mountain, Namong Island, Kelaki Island, Kima Island, Komodo, wild horses and buffalo, savannah, Rangka Cave, Gosong, Pasir Timbul, Mangrove and several underwater object such as Manta and coral reefs. (2) Based on a quantitative strategy, the development strategy that is suitable to be carried out in Labuan Bajo is the S-O Strategy which is carried out by utilizing the strength needed to achieve the opportunities that exist. (3) Based on a qualitative strategy, a suitable strategy to be carried out in Labuan Bajo is related to the improvement of public facilities, partnerships with universities, improvement of the people's economy, and the improvement of regional and group economies. Keywords: Community based tourism, local communities, natural resources, potencies, SWOT analysis